LECTURER PROFESSIONAL DEVELOPMENT PROGRAM STRATEGIES AT PUBLIC STATE UNIVERSITY - Rohman, Abdul (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
The purpose of this study was to describe the lecturer professional development program strategies. The data was collected by conducting interviews, observations, and documentation. The informants in this study were the member of university senate, rector, vice rector, the head and secretary of quality assurance institutions, the head and secretary of research and community service institution. The data analysis was done through a single case data analysis. The result of this study showed that the strategies used by state university in lecturer development program focusing on the noble values of the university's long-term strategic plans. There were authorized institutions, established groups of expertise field, guidebooks for lecturers’ management, and the development philosophy. The strategies in developing the lecturer professionalism on education and teaching were done by sending them for further study a doctoral degree, giving assistance, conducting pedagogical workshop, foreign language workshop, in-service training, and integrated workshop. On the research field, qualitative and quantitative research workshop were conducted. Creating orientation on research development, research scheme, classification and funding. On the community service field, lecturer professional development program was done by debriefing and forming a community-based service.